Pooling Fiscal Risk in the ECCU : Quantifying Savings of a Regional Fund for Stabilization and Investment - Guerson, Alejandro (IMF Working Papers; Working Paper ;, 2021)
This paper quantifies the savings obtained from risk pooling with a Regional Stabilization Fund (RSF) for the Eastern Caribbean Currency Union. A Monte Carlo experiment is used to estimate the size of a RSF conditional on probabilities of depletion under specific saving-withdrawal rules. Results indicate that regional risk pooling requires about half of the saving amount relative to the sum of individual-country savings. In addition to reducing the amount of saving requirements for stabilization, the RSF can improve welfare by realocating government consumption savings during booms towards public investment during recessions, resulting in an increase of public investment in the range of 0.5-1.5 percent of GDP per year depending on the country, with positive growth dividends. Moreover, the RSF also reduces the dispersion of public debt outcomes in light of the cross-country cyclical synchronicity of output and revenue, thereby strengthening the stability of the regional currency board.